2017
DOI: 10.1177/0954008317740194
|View full text |Cite
|
Sign up to set email alerts
|

POSS-benzocyclobutene (POSS-BCB) resin

Abstract: Organic-inorganic hybrid materials with a high thermal stability and a low dielectric constant show great potential in the microelectronics industry. In this work, polyhedral oligomeric silsesquioxane-benzocyclobutenes (POSS-BCBs) were synthesized by a hydrosilylation reaction of octavinyloctasilasesquioxane (OVPOSS) and 4-(1,1-dimethyl-1-hydro)-silyl-benzocyclobutene with H2PtCl6 as a catalyst. The ring-opening reaction of BCB on POSS-BCBs resulted in POSS-BCB resins with a highly cross-linked network structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…The selection of BCB to functionalize POSS is because it is a weakly polarized group and can be directly converted to polymer networks with excellent thermo‐mechanical properties, relatively low k values and good hydrophobicity. [ 52,53 ] Although it has been applied for partially modification of T 8 POSS and double‐decker silsesquioxane, [ 54,55 ] T 8 , T 10 , and T 12 POSS with fully functionalized BCB groups have never been reported. Our results indicate that the k values of obtained materials are linearly reduced ( k = 2.24 for c ‐T 8 B 8 , 2.02 for c ‐T 10 B 10 , and 1.83 for c ‐T 12 B 12 ) but other properties such as thermal stability, mechanical properties, surface smoothness and hydrophobicity do not show any decline (even slightly enhance) with increasing the cage volumes.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of BCB to functionalize POSS is because it is a weakly polarized group and can be directly converted to polymer networks with excellent thermo‐mechanical properties, relatively low k values and good hydrophobicity. [ 52,53 ] Although it has been applied for partially modification of T 8 POSS and double‐decker silsesquioxane, [ 54,55 ] T 8 , T 10 , and T 12 POSS with fully functionalized BCB groups have never been reported. Our results indicate that the k values of obtained materials are linearly reduced ( k = 2.24 for c ‐T 8 B 8 , 2.02 for c ‐T 10 B 10 , and 1.83 for c ‐T 12 B 12 ) but other properties such as thermal stability, mechanical properties, surface smoothness and hydrophobicity do not show any decline (even slightly enhance) with increasing the cage volumes.…”
Section: Introductionmentioning
confidence: 99%
“…have been considered as ideal pore generators for reducing the materials' k values. [15,[25][26][27][28][29][30][31][32] Meanwhile, the organic-inorganic hybrid nature and high reactivity of POSSs endow the resulting materials high thermal [28,[32][33][34][35] and mechanical performance, [36,37] large surface area and pore volume, [38][39][40][41] and unique surface properties. [42,43] Recently, we demonstrated that larger POSS (i.e., T 10 and T 12 POSSs) is better nano-building block and filler for fabricating thermally and mechanically robust low-k materials.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] For decades, researchers have focused on improving the thermostability of resins by introducing rigid groups such as phenyl, 20,21 norbornyl, 22,23 and adamantyl 24,25 groups into the Si-O-Si main chain or side chains. Permittivity can be reduced by introducing fluorine groups [26][27][28] or cage structures 18,29,30 by hydrosilylation and/ or Heck reactions. The introduction of rigid groups improves the thermal stability of BCB resin to a certain extent, but reduces its molecular flexibility.…”
Section: Introductionmentioning
confidence: 99%